Effect of Tween 80 Concentration on the Physicochemical Characteristics of Strawberry (Fragaria × ananassa) Fruit Extract Nanoemulsion - Dwi Saryanti; Suharyanto; Livi Melati Andini Putri (Jurnal Riset Kefarmasian Indonesia, 2026)
Strawberries (Fragaria x ananassa Duch.) contain non-polar flavonoids and function as antioxidants. Nanotechnology can increase drug bioavailability, has a kinetically stable system, has the ability to penetrate deeper into the skin, lowers viscosity, and delivers the active substance to the skin surface to form a thin layer. The purpose of this study was to observe the effect of Tween 80 as a surfactant on the fruit extract nanoemulsion formulation. Nanoemulsion is made from Tween 80 surfactant, PEG 400 cosurfactant, and virgin coconut oil oil phase. The concentration of Tween 80 used by F1, F2, and F3 was 20%, 30%, and 40%. The preparations were tested for organoleptic properties, pH, viscosity, transmittance and droplet size on the formula with the smallest droplet size. The organoleptic of the resulting nanoemulsion is in the form of a clearer brown colour, a characteristicic odour, and a, and a liquid form,form, and there is no separation phase. The effect of varying the concentration of Tween 80 in the nanoemulsion formulation of strawberry fruit extract: the higher the concentration of Tween 80, the higher the pH value, % transmittance and viscosity of the preparation. The droplet sizes on F1, F2, and F3 were 5722.77 ± 1.53 nm, 3328.5 ± 0.00 nm, and 25.97 ± 0.90 nm with a polydispersity index of 16.312 ± 4.32, 9.927 ± 0.00, and 1.060 ± 0.11. Nanoemulsions of strawberry fruit extract with a concentration of 40% can produce good preparations. The antioxidant testing findings utilising the ABTS method revealed that the strawberry extract nanoparticle formulation exhibited an IC50 value of under 50, signifying exceptionally potent antioxidant activity.